Economic evaluation of using polygenic risk score to guide risk screening and interventions for the prevention of type 2 diabetes in individuals with high overall baseline risk - Martikainen, Janne; Lehtimäki, Aku-Ville; Jalkanen, Kari; Lavikainen, Piia; Paajanen, Teemu; Marjonen, Heidi; Kristiansson, Kati; Lindström, Jaana; Perola, Markus (Frontiers in Genetics, 2022)
Type 2 diabetes (T2D) with increasing prevalence is a significant global public health challenge. Obesity, unhealthy diet, and low physical activity are one of the major determinants of the rise in T2D prevalence. In addition, family history and genetic diabetes risk also play a role in the development of T2D. Therefore, solutions for early identification of individuals at high risk for T2D for early targeted detection of T2D, prevention, and intervention are highly preferred. Recently, novel genomic-based polygenic risk scores (PRSs) have been suggested to improve the accuracy of risk prediction supporting the targeting of preventive interventions to those at highest risk for T2D. Therefore, the aim of the present study was assessing the cost-utility of an additional PRS testing information (as a part of overall risk assessment) followed by a lifestyle intervention and additional medical therapy when estimated 10-year overall risk for T2D exceeded 20% among individuals screened being in high-risk category (i.e., 10-20% 10-year overall risk of T2D) based on traditional risk factors only. For a cost-utility analysis, an individual-level state-transition model with probabilistic sensitivity analysis was constructed. A one-year cycle length and a lifetime time horizon were applied in the base-case. A 3% discount rate was used for costs and QALYs. Cost-effectiveness acceptability curve (CEAC) and estimates for the expected value of perfect information (EVPI) were calculated to assist decision makers. The use of the targeted PRS strategy re-classified 12.4 percentage points of individuals to be very high-risk individuals who would have been originally classified as high risk using the usual strategy only. Over a lifetime horizon, the targeted PRS was a dominant strategy (i.e., less costly, more effective). One-way and scenario sensitivity analyses showed that results remained dominant almost in all simulations. However, there is uncertainty, since the probability (EVPI) of cost-effectiveness at a WTP of 0€/QALY was 63.0% (243€) indicating the probability that the PRS strategy is a dominant option. In conclusion, the results demonstrated that the PRS provides moderate additional value in risk screening leading to potential cost savings and better quality of life when compared with the current screening methods for T2D risk.